356-OR: Accuracy Evaluation of an Implantable CGM with Chemistry Improvements in a 365-Day Feasibility Study - AL-KHAWI, LUJAIN; SANCHEZ, PATRICIA; HUFFSTETLER, PHILIP; VELVADAPU, VENKATA N.; MASCIOTTI, JAMES M.; TWEDEN, KATHERINE S.; KAUFMAN, FRANCINE R. (Diabetes (New York, N.Y.), 2023)
Background: The prospective, multi-center PROMISE study demonstrated safety and accuracy of the 180-day Eversense E3 CGM System in adults with diabetes. Subsequently, the implantable E3 CGM sensor material and protective chemistries were advanced to improve the sensor signal maintenance. This analysis compares this Modified CGM System accuracy obtained from a feasibility study to that of the E3 CGM System using data from the PROMISE study. Methods: A 365-day feasibility study was conducted to assess accuracy of CGM to SMBG measurements using the CONTOUR Next One meter for 32 Modified E3 sensors inserted in 32 subjects through 365 days. Results were compared to the CGM-SMBG pairs of E3 sensors from 30 subjects evaluated in the PROMISE study through 180 days. Results: Modified E3 CGM System accuracy to SMBG through day 365 was equivalent to that of the E3 CGM System through day 180 as shown in the Table below. Table: Accuracy to SMBG measurements of the Modified E3 sensors compared to that of E3 control sensors (Mean MARD increase of ~1.4% when SMBG is used as reference compared to YSI) Conclusion: Modifications to the E3 sensor prolonged the longevity of the sensor from 180 days to 365 days while maintaining accuracy, suggesting that a fully implanted CGM System could provide accurate data over a one-year time period.